Were Mankiw, Romer, and Weil right? A reconciliation of the micro and macro effects of schooling on income. (2013)
In Mankiw, Romer, and Weil's augmented Solow model [Quarterly Journal of Economics 107 (2) 407–437 (1992)], the marginal product of human capital accrues to three factors of production: directly to human capital, and as an external effect to physical capital and labor. This paper estimates national stocks of human capital in 1990 created from prior investment in schooling and shows that for 36 countries the (macro) marginal product of human capital accruing to workers in 1990 is consistent with estimates of the (micro) marginal return on investment in schooling in workers' earnings studies. This reconciliation provides empirical evidence for the augmented Solow model.